ЭКОНОМИЧЕСКОЕ СОДЕРЖАНИЕ ФИНАНСОВОЙ УСТОЙЧИВОСТИ ПРЕДПРИЯТИЯ В СОВРЕМЕННЫХ УСЛОВИЯХ (Journal of Economic Research & Business Administration, 2015)
In article the review of interpretation of the financial sustainability by various authors and own definition are given.